2018
DOI: 10.26434/chemrxiv.6349253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of Phosphoranyl Radicals via Photoredox Catalysis Enables Voltage–Independent Activation of Strong C–O Bonds

Abstract: Alcohols and carboxylic acids are ubiquitous functional groups found in organic molecules that could serve as radical precursors, but C–O bonds remain difficult to activate. We report a synthetic strategy for direct access to both alkyl and acyl radicals from these ubiquitous functional groups via photoredox catalysis. This method exploits the unique reactivity of phosphoranyl radicals, generated from a polar/SET crossover between a phosphine radical cation and an oxygen centered nucleophile. We first show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…25). 49 They adopted this polar/SET crossover reaction platform in the direct deoxygenation of both alcohols and carboxylic acids (Fig. 25a, 171).…”
Section: Photo-induced Radical Reactions Of Tertiary Phosphines With mentioning
confidence: 99%
“…25). 49 They adopted this polar/SET crossover reaction platform in the direct deoxygenation of both alcohols and carboxylic acids (Fig. 25a, 171).…”
Section: Photo-induced Radical Reactions Of Tertiary Phosphines With mentioning
confidence: 99%
“…Thus, the combination of these three elementary steps has not been exploited to effect catalytic C−O activation. 26,27…”
mentioning
confidence: 99%
“…Cross coupling of fluoro-, chloro-, or iodo-substituted aryl bromides produced the corresponding products 25-29 in moderate to good yields with retention of F, Cl, and I on the aryl ring, providing additional reaction cite for further synthetic elaborations of the ester products. 109 In addition, we found that this photoredox Ni-catalyzed radical coupling reaction tolerates a variety of heteroaryl groups, including pyridine (30-32), quinoline (33 and 34), isoquinoline (35), benzothiophene (36), indole (37), 7-azaindole (38), and indazole (39). Selective coupling of the corresponding heteroaryl bromides Page 8 of 25 CCS Chemistry and hemioxalates leaded to the desired esters 30-39 in moderate to good yields.…”
Section: Scope Of the Reactionmentioning
confidence: 99%